Multiculturalism as a Character Education Strategy in Responding to Social Conflict and Challenges to National Integration in Indonesia - Dafril Dafril; Mahyudin Ritonga; Julhadi Julhadi (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2026)
Indonesia, as a multicultural nation, faces serious challenges marked by the increasing prevalence of identity-based social conflicts, intolerance, and social polarization, which have contributed to the weakening of national integration. This condition indicates that the management of diversity cannot rely solely on symbolic or repressive approaches, but requires educational and sustainable strategies. This article aims to analyze multiculturalism as a character education strategy in responding to social conflicts and the challenges of national integration in Indonesia. The study employs a qualitative approach using library research methods through critical analysis of academic literature, research findings, and relevant policy documents. The findings reveal that multicultural-based character education plays a strategic role in fostering tolerant attitudes, strengthening social cohesion, and cultivating an inclusive national identity without negating local identities. When systematically integrated into curricula, school culture, and learning practices, multiculturalism functions as a preventive approach to social conflict and serves as a foundation for sustainable national integration. This article contributes to the enrichment of character education studies by positioning multiculturalism as a strategic framework contextualized to Indonesia’s socio-cultural realities in the twenty-first century.